The Krasnoborsky population of the European bison: history of emergence, present state, and growth perspectives - Kashtalian, A. (Theriologia Ukrainica, 2019)
A new free-living population of the Bialowieza bison (Bison bonasus bonasus L., 1758) emerged in 2015 in the northern part of Belarus, in the territory of the Verkhnedvinsky and Rossonsky districts, Vitebsk region, Belarus. We had been monitoring the population for four years, from the moment of its emergence until the beginning 2019. Visual bison observations, search for traces of their vital activity, questionnaires of rangers and local peoples were used for data collection. Information was accumulated on population dynamics, fertility, mortality, age and sex structure, seasonal characteristics of the spatial and territorial structure of herds and small groups. There was a rapid increase in the number of animals at the initial stage of the Krasnoborsky population’s existence. This can be explained by the large number of introduced bison founders (68 individuals), high birth rates, low mortality, and predominance of young and middle-aged animals (about 87 % of the total abundance). The population’s abundance reached 155 individuals by the beginning of 2019. It is characterised by the predominance of females over males in a ratio of 1.84 : 1. The Krasnoborsky population consists of two territorial groups. Each of them has several herds, which are extremely unstable by their abundance, seasonal, and sex structure. The area on which the population lives exceeds 17 thousand hectares. Bison use this territory unevenly. Key habitats, regular migration routes and rarely visited areas are highlighted. Adult males often leave the habitat of the population and move from its territory for a long time. Practical measures are indicated, the implementation of which will contribute to the long-term conservation of the Krasnoborsky population. The main directions of ensuring the population’s existence are creation of a functional system of its livelihoods, including a complex of biotechnical, conservational, preventive veterinary measures, and genetic control. To achieve this goal it is necessary to develop and implement a management plan for the Krasnoborsky population. У 2015 році в північній частині Білорусі, на території Верхньодвінського та Росонського районів Вітебської області створено нову вільноживучу популяцію біловезького зубра (Bison bonasus bonasus L., 1758). Протягом чотирьох років (з моменту виникнення до початку 2019 р.) автор здійснював регулярний моніторинг її стану. Проводилися візуальні спостереження за тваринами, пошук слідів життєдіяльності, анкетування та опитування єгерів та місцевого населення. Йшов збір даних з динаміки чисельності популяцій, народжуваності, смертності та статевовікового складу зубрів, сезонних особливостей просторової та територіальної структури стад та окремих особин. Початковий етап існування красноборської популяції характеризується швидким кількісним ростом. Це пояснюється чисельністю завезених зубрів-засновників (68 особин), високою народжуваністю молодняка, низькою смертністю та переважанням в популяції молодих та середньовікових тварин (близько 87 % від загального поголів'я). До початку 2019 року чисельність популяції сягнула 155 особин. Територіально красноборська популяція складається з двох груп, кожна з яких сформована кількома стадами, що доволі нестабільні за своїм кількісним та статевовіковим складом. Площа її сучасного ареалу перевищує 17 тис. га. Ця територія використовується зубрами нерівномірно: на ній виділяються ключові місця проживання, шляхи регулярних міграцій та мало відвідувані ділянки. Частина дорослих самців мігрує на довготривалий період за межі популяційного ареалу. Пропонується комплекс практичних заходів, реалізація яких буде сприяти довготривалому збереженню красноборської популяції. Основні зусилля слід направити на створення функціональної системи її життєзабезпечення, яка включає заходи біотехнічної, охоронної та ветеринарно-профілактичної спрямованості та регулярний генетичний контроль. Досягненню цієї мети буде сприяти також розробка та впровадження плану управління красноборською популяцією.